(untitled) (Research, Society and Development, 2021)
The great popularity of brachycephalic dogs among tutors led to the need for greater knowledge on the part of veterinarians about the characteristic diseases of these breeds. Particularly noteworthy are the modifications related to the anterior airways, which have undergone major changes and predispose to the development of a severe multisystem disease known as brachycephalic dog syndrome (SB) or obstructive respiratory syndrome of the brachycephalic (BOAS). The present study aims to present a literature review highlighting the clinical and anatomical aspects of BS considering the importance of this disease in the medical and surgical clinic of small animals. Thus, it can be concluded that the early recognition of the obstructive anatomical changes that characterize the brachycephalic syndrome by the veterinarian is extremely important for the prompt institution of the treatment, enabling better results and thus better quality of life for the animal.